Paragenetic sequences, hydrothermal alterations and fluid inclusions of the Bienaventurada - Huachocolpa - Huancavelica vein - Yparraguirre Calderón, José Andrés (2012)
The Bienaventurada vein is located within the mining District of Huachocolpa, department of Huancavelica at 4550 m above sea level, in volcanic rocks of Neogene corresponding to the formation «Domos de Lava»; they are fundamentally andesites. They strike is N52º - 65ºE and dip 55º - 75º, the potent of this vein is variable 1 - 4m. The mineral filling has a hydrothermal origin, of the epithermal reach located by processes of stuffed of fissure with breach. Studies of fluid inclusions suggest that two types of fluids were implicated. The first, with salinities between 5-8% NaCl and homogenization temperatures between 220-230ªC; whereas diluted other (1,5-4% NaCl) is in the external parts with homogenization temperatures between 298-300ªC. Both show boiling evidences. The mineralogical association consists on pyrite, which was the first mineral deposited in the structures; the quartz, another abundant mineral with a long period of mineralization; followed by the sphalerite, chalcopyrite, tetrahedrite, galena, lead sulfosalts and barite; and later realgar and orpiment. The second sequence this constituted by pyrite, tetrahedrite, lead sulfosats and stibnite. Finally it is possible to observe a supergene mineral sequence constituted by melnicovite, anglesite, gysum, hematite and limonite. The mineral distribution that presents the vein is vertical; with Ag values predominating in depth, while the zinc and lead are increased in upper levels. They present halos of hipogene wallrock alteration, constituted by argilization, silicification, sericitization and k-adularia alteration.